STRATEGI PENGHULU DALAM RANGKA MEMBENTUK KELUARGA SAKINAH MAWADDAH WARAHMAH MELALUI KHUTBAH NIKAH (STUDI KASUS DI KUA LOWOKWARU)STRATEGI PENGHULU DALAM RANGKA MEMBENTUK KELUARGA SAKINAH MAWADDAH WARAHMAH MELALUI KHUTBAH NIKAH (STUDI KASUS DI KUA LOWOKWARU) - Meylinda Rosyidah; Khoirul Asfiyak; Dzulfikar Rodafi (Jurnal Hikmatina, 2022)
Generally, the marriagee sermon only provides advice to the bride and groom and the people present to achieve the goal of forming a sakinah mawaddah warahmah family. This study aims to describe the strategy used by the head of the KUA Lowokwaru Malang to distribute knowledge in building a sakinah family through marriage sermons and describe the inhibiting and supporting factors in delivering the marriage sermon. This research used a qualitative approach. The type of research was a case study whose respondents were through data collection such as observation, interviews, and documentation. This study indicates that the strategy of the head of KUA Lowokwaru Malang in forming a sakinah family is through marriage guidance, routine counseling by BP4, and the sakinah heritage program through interpersonal communication strategies and the use of good language. Supported by the penghulu's knowledge in delivering the marriage sermon. Moreover, the inhibiting factors are the personality of the different penghulu and constraints on the number of marriages. The conclusion of this study is to look at the condition of human resources at KUA Lowokwaru. It is necessary to hold a more in-depth briefing and add more professional human resources to implement the sakinah family coaching program.Keywords: Strategy, sakinah family, marriage sermon